Ideal Model in Law: Journalists and Application in Press Reporting - Mustawa Mustawa; Abd. Haris Hamid; Handar Subhandi Bakhtiar; Andi Musran; Asriadi Asriadi; Syukri Masse (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2025)
The appointment of journalists, especially in the field of legal coverage, is extremely urgent and has a wide- ranging impact on conveying information containing truth values, in order to realize a free and responsible press. The manifestation of this responsibility, however, is not accompanied by a system for the appointment of journalists, leading to the dissemination of information that triggers inaccuracies in news, resulting in legal claims, both criminal and civil. These claims continue to occur, and the number of journalists entangled in legal issues also continues to increase. All of this is caused by laxity, both in Law Number 40 of 1999 and in the Press Council Regulations, which do not regulate the standards for the appointment of the journalistic profession. This laxity has triggered the idea of creating a system for the appointment of legal journalists based on the affirmation of a profession that meets professional standards through an ideal model, the regulation of which lies within a legal framework. ___ References Books with an author: Gant, S. (2007). We're all journalists now: The transformation of the press and reshaping of the law in the internet age, New York: Free Press. Haltom, W., & McCann, M. Distorting the Law: Politics, Media, and the Litigation Crisis, Chicago: The University of Chicago Press. Kolodzy, J. (2006). Convergence journalism: Writing and reporting across the news media. NY: Rowman & Littlefield. Manning, P. (2000). News and news sources: A critical introduction, UK: De Montfort University. McNair, B. (2006). Cultural chaos: journalism and power in a globalised world. London: Routledge. Mustawa. (2020). Hukum Pemberitaan Pers, Sebuah Model Mencegah Kesalahan Berita, Jakarta: Kencana (Prenada Media Grup). Plaisance, P. L. (2013). Media ethics: Key principles for responsible practice, LA: Sage Publications. Waisbord, S. (2013). Reinventing professionalism: Journalism and news in global perspective. UK: Polity Press. Journal articles: Akbar, A., Mannan, K., & Saputra, I. R. (2023). Kajian Yuridis Terhadap Tindakan Pencemaran Nama Baik. Jurnal Litigasi Amsir, 150-156. http://journalstih.amsir.ac.id/index.php/julia/article/view/260 Ambarwati, A., Rahman, S., Qahar, A., & Poernomo, S. L. The Essence of the Principle of Good Faith in the Agreement For The Parties. IOSR Journal of Humanities and Social Science, 27, 36-43. https://doi.org/10.9790/0837-2708063643 Astuti, T., Purwanda, S., Prasisto, J., & Prayudi, P. (2024). PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEREDARAN OBAT TANPA IZIN EDAR:(Studi Putusan Nomor 1/Pid. Sus/2023/Pn. Pre). Jurnal Hukum Positum, 9(1), 1-16. https://journal.unsika.ac.id/positum/article/view/11132 Balla, H., Jumardin, J., Kasim, A., & Pappa, A. K. (2024). Peran Locus dan Tempus Delicti dalam Menentukan Kompetensi Pengadilan pada Kasus Kejahatan Siber. Jurnal Litigasi Amsir, 11(4), 390-395. https://journalstih.amsir.ac.id/index.php/julia/article/view/564 Djanggih, H., Syam, E. S., & Gunawan, S. (2023). The Prosecutor's Legal Policy In Enacting Restorative Justice On Criminal Case. Russian Law Journal, 11(3), 1349-1357. http://repository.umi.ac.id/2370/ Ettema, J. S. (2007). Journalism as reason-giving: Deliberative democracy, institutional accountability, and the news media's mission. Political Communication, 24(2), 143-160. https://doi.org/10.1080/10584600701312860 Gollmitzer, M. (2023). Journalism ethics with Foucault: Casually employed journalists’ constructions of professional integrity. Journalism, 24(5), 1015-1033. https://doi.org/10.1177/14648849211036301 Kasim, A., Suhariyanto, D., Ramdhani, W., Rahim, E. I., & Danial, D. (2024). Scenarios For Limiting The Veto of Permanent Members Of The United Nations Security Council. Pena Justisia: Media Komunikasi dan Kajian Hukum, 23(1), 499-517. https://jurnal.unikal.ac.id/index.php/hk/article/view/4163 Mustawa, M. (2019). Journalist Competence in Applying the Presumption of Innocence Principle on Press Release. Amsir Law Journal, 1(1), 36-42. https://doi.org/10.36746/alj.v1i1.20